Optimizing Students' Entrepreneurial Interest - Humairoh Humairoh; Mohammad Annas (Dinasti Publisher, 2023)
The aim of this studies is to determine simultaneously the influence of the usage of e-commerce, entrepreneurship education, and gender on students' entrepreneurial interest and to determine the differences in entrepreneurial interest of male and female college students. This studies makes use of number one statistics using a questionnaire disbursed to college students of the management take a look at program, school of Economics and business, Muhammadiyah university, Tangerang. The approach used on this research is a quantitative approach with a comparative descriptive studies layout. The research population, specifically students from the management study program, faculty of Economics and business, Muhammadiyah university, Tangerang, numbered 1,950 students. the entire sample was 100 students. The sampling method was random sampling for students in semesters III, V, VII. data analysis strategies with the assist of SPSS software. This studies suggests that simultaneously there's a positive and significant impact of using e-commerce, entrepreneurship education, and gender on students' interest in entrepreneurship and there may be a significant difference in interest in entrepreneurship between male and woman college students.